Correlation of Beta Angle and Wits Appraisal with ANB Angle in the Evaluation of Sagittal Skeletal Discrepancy (Orthodontic Journal of Nepal, 2024)
Introduction: Different cephalometric parameters are used to assess sagittal skeletal discrepancy including ANB angle, Wits appraisal and Beta angle. This study aimed to determine the Beta angle measurement in the study population and correlate it with the ANB angle, along with a comparison of Wits appraisal and ANB angle for the validity and reliability of the Beta angle.Materials and Methods: A comparative observational study was carried out on 114 participants (45 males and 69 females) aged 10 to 35 years. ANB angle, Wits Appraisal and Beta angle from the lateral cephalogram were used for the assessment of sagittal skeletal discrepancy. Ten percent of the cephalograms were randomly selected, retraced and re-analyzed by the investigator, and two readings were compared for reliability. The mean and standard deviation of the Beta angle were obtained for different skeletal patterns. Pearson’s correlation test and multiple regression analysis (stepwise) were used to measure the significance level. Finally, an independent t-test was used to determine differences between the study population and Caucasian norms.Results: The mean values of the Beta angle for class I was 34.99˚, for class II was 28.84˚, and for class III was 49.66˚. There were significant differences between obtained values for different skeletal patterns (p